Land Acquisition Strategy of PT Krakatau Industrial Estate Cilegon to Acquire Land with Reasonable Price and Without any Future Problem - Maryono, Maryono; Soedjarno, Alibasjah I (The Indonesian Journal of Business Administration, 2013)
As an industrial estate company PT KIECâ€™s performance still very dependent on the industrial land sales. Ratio of land sales to non-land sales was around 70:30 and the ratio of land and non-land profit is 85:15. With this business profile condition, PT. KIEC faced a problem with land banking that becomes very limited. Balance of the land to be sold by December 2012 was 80 ha. This condition is feared could disrupt corporate business sustainability. PT. KIEC must immediately undertake land acquisition proces, but until the end of year 2012 the process cannot run well. It faced many obstacles such as limited land supply, land allocated as industrial area occupied by resident, the existence of land speculators, land acquisition method, ability to approach the society and limited fund. To start land acquisition, KIEC needs to analyze and decide the location and release the strategy which is considering the existing obstacles. Site location selection is done through a rating analysis of several alternative locations. The primary parameters to be analyzed are land allotment base on the spatial planning, site potential to grow, accessibility, availability of infrastructure and utilities, availability of waste water receiving bodies, land contours, distance from housing, current land use and land prices. Besides, it also conducted a brief study of the feasibility study, which calculates estimated investment cost and its returns. From the several location alternatives, it was selected two priority locations, those are Tegalratu andÂ Makamaja village, with potential land to be acquired are 70 ha and 40 ha respectively. But only Tegalratu location will be deployed in detail. Land acquisition strategy is prepared by considering the analysis of legal aspects, social aspects and risk analysis. Transactions of land acquisition should be done with the legitimate owners of the land, as evidenced by certificate of ownership (underlying right). In order to do land acquisition quickly, it needs to learn the characteristics of the relevant stakeholders. And to minimize the things that are not desirable in the future, it needs to conduct risk analysis to map the potential risks and its mitigation measures. By considering these things hence land acquisition is done by using the services of an arranger. Land price is estimated by considering land transaction price around the location in recent month and analyzed further by appraiser consultant To acquire the land at Tegalratu village with total area 70 ha, it needs investment cost about Rp. 176 billions and it will take time about 1 year. The executor of land acquisition is an arranger that needs to be selected further. And as a partner from the internal is Land acquisition team of PT. KIEC.Â Keywords: land acquisition, prudent, fair price